Beitrag zur Kenntnis der Eier der Tingiden (Heteroptera: Tingidae). - Štusák, Josef Miroslav (Contributions to Entomology = Beiträge zur Entomologie, 1957)
There are described the eggs unknown hitherto of 4 species of Tingidae. The way of deposition of eggs into the tissue of the food-plant in Lasiacantha capucina Germ., Catoplatus carthusianus Goeze, and Tingis grisea Germ. As found to agree with the type of oviposition called "profund-implantiert" by Michalk 1935. In Tingis reticulata H.-S. the eggs of which were available only by dissection of a female, oviposition could not be observed. The eggs of these species differ by the structure of the micropylar-apparatus, which may be of taxonomic value.